2000
DOI: 10.1542/peds.105.2.e19
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Dosing Frequency on the Efficacy of 10-Day Penicillin or Amoxicillin Therapy for Streptococcal Tonsillopharyngitis: A Meta-analysis

Abstract: ABSTRACT. Objective. The recommended dosing frequency of oral penicillin for the treatment of acute streptococcal tonsillopharyngitis has long been 3 to 4 times daily. In 1994, treatment guidelines included twicedaily (BID) dosing for the first time, a recommendation that could significantly increase the ease of compliance. This meta-analysis was performed to determine whether overall cure rates differed between BID or once-daily (QD) versus more frequent dosing schedules in the treatment of streptococcal tons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
3

Year Published

2003
2003
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(14 citation statements)
references
References 33 publications
0
10
0
3
Order By: Relevance
“…Then, the original data set was simulated 100 times and the time during which the plasma concentration of every original neonate was above the MIC was calculated. If a treatment regimen was found that did not attain the target in more than 50% of patients, we considered increasing the dose and/or frequency and the optimal dosing regimens were given to virtual patients (Visser et al, 1993;Lan and Colford, 2000;Drusano, 2003). The target achievement probability of each regimen was calculated to select the optimal regimen.…”
Section: Dosing Regimen Evaluation and Optimizationmentioning
confidence: 99%
“…Then, the original data set was simulated 100 times and the time during which the plasma concentration of every original neonate was above the MIC was calculated. If a treatment regimen was found that did not attain the target in more than 50% of patients, we considered increasing the dose and/or frequency and the optimal dosing regimens were given to virtual patients (Visser et al, 1993;Lan and Colford, 2000;Drusano, 2003). The target achievement probability of each regimen was calculated to select the optimal regimen.…”
Section: Dosing Regimen Evaluation and Optimizationmentioning
confidence: 99%
“…cilina que pueden alcanzarse en vivo, por espectro reducido y por coste económico 38 . La administración de penicilina, no obstante, resulta incómoda por los preparados disponibles y las pautas recomendadas, aunque puede facilitarse su uso empleando pautas de 2 dosis diarias 39 o, en casos de cumplimiento dudoso, administrando penicilina benzatina por vía intramuscular. Amoxicilina constituye una alternativa razonable, es un antibiótico de amplio uso en España y con excelente tolerancia.…”
Section: Análisis Global De Frecuencias De Las Principales Variablesunclassified
“…Although antibiotic dosing regimens have been investigated for more than half a century [1], we do not yet have a sufficient understanding of the link between drug dosing and bacterial killing to design rational treatment strategies [2, 3]. Even for antibiotic regimens that have been standard of care, substantial improvements in dosing levels [4], treatment frequency [5] and treatment duration[6–8] have been made decades after their introduction. Most experimental and some clinical studies investigate antibiotic concentrations at a constant or at an average concentration.…”
Section: Introductionmentioning
confidence: 99%